CHSY1 promotes aggressive phenotypes of hepatocellular carcinoma cells via activation of the hedgehog signaling pathway. (10th September 2017) - Liu, Chiung-Hui; Lan, Chyn-Tair; Chou, Jui-Feng; Tseng, To-Jung; Liao, Wen-Chieh
Abstract: Abnormal expression of chondroitin sulfate has been found in many types of cancer, while its biological functions in hepatocellular carcinoma (HCC) progression remain uninvestigated. Here, we report that chondroitin sulfate synthase 1 (CHSY1), the enzyme that mediates the polymerization step of chondroitin sulfate, is a critical mediator of malignant character in HCC that acts via modulating the activity of the hedgehog signaling. CHSY1 was up-regulated frequently in HCC where these events were associated with worse histologic grade and poor survival. Enforced expression of CHSY1 was sufficient to enhance cell growth, migration, invasion, and epithelial-mesenchymal transition, whereas silencing of CHSY1 suppressed these malignant phenotypes. Mechanistic investigations revealed that the increase of cell surface chondroitin sulfate by CHSY1 promoted sonic hedgehog binding and signaling. Inhibiting hedgehog pathway with vismodegib decreased CHSY1-induced migration, invasion, and lung metastasis of HCC cells, establishing the critical role of hedgehog signaling in mediating the effects of CHSY1 expression. Together, our results indicate that CHSY1 overexpression in HCC contributes to the malignant behaviors in cancer cells, we provide novel insights into the significance of chondroitin sulfate in hedgehog signaling and HCC pathogenesis. Highlights: Up-regulation of CHSY1 endowed HCC with poor prognosis and malignant cellular behaviors. Silence of CHSY1 suppressed malignant cellular behaviors in HCC cells. CHSY1 promoted hedgehog signaling in vitro and in vivo. Inhibition of hedgehog signaling suppressed CHSY1-induced malignant phenotypes.